KESANTUNAN BERBAHASA DIKALANGAN REMAJA DALAM KEHIDUPAN BERMASYARAKAT DI GAMPONG DAYAH SEUMIDEUN, KECAMATAN PEUKAN BARO, KABUPATEN PIDIE - Sayed Muhammad; Vera Wardani; Nuraiza Nuraiza (Fakultas Keguruan dan Ilmu Pendidikan Universitas Jabal Ghafur, 2025)
ABSTRACTThis study aims to describe the form of language politeness among teenagers and analyze the factors that influence the politeness in social life in Gampong Dayah Seumideun, Peukan Baro District, Pidie Regency. The method used is a case study with a qualitative descriptive approach. Data were obtained through observation, interview, and documentation of teenagers aged 15-19 years. The results showed that teenagers tend to use relaxed and informal language in daily conversations, even often interspersed with harsh expressions. The use of linguistically polite language, such as apologizing or showing empathy, is rarely found, except in formal situations or when talking about topics that are considered important, such as education. The main factors influencing the low level of language politeness are the free friendship environment, lack of parental supervision, weak character education at school, and the influence of popular culture and social media. This phenomenon has an impact on social relationships, teenagers' self-image, and the preservation of local cultural values. This study emphasizes the need for collaboration between families, schools, and communities to instill the values of language politeness consistently, in order to form polite and ethical adolescent characters in social life. Keywords: Language politeness, adolescents, social factors, character education, popular culture.